Optimalisasi Peningkatan Keterampilan Kelompok Perempuan Aisyiyah dalam Pemanfaatan Lahan Kebun untuk Memenuhi Kebutuhan Sayuran yang Sehat dan Aman: Optimization of Increasing the Skills of the Aisyiyah Women’s Group in Use of Garden Land to Fulfill the Need for Healthy and Safe Vegetables - Dewi, Sukuriyati Susilo; Mulyono, Mulyono; Hartanto, Tri; Ngafwan, Ngafwan (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Insights and skills in the intensification of yard land to be more productive and provide added value to the community, and the potential of human and natural resources in Gamping District. To achieve the predetermined objectives, methods have been carried out, namely, counseling, which is carried out by gathering organizational leaders and worshipers to attend counseling on women's empowerment, yard land management, and technology for utilizing family waste into organic fertilizer, with resource persons from the Implementation Team, Demonstrations and training are carried out by simulating healthy vegetable cultivation practices using equipment and materials that have been prepared by program implementers, cultivation practices by utilizing the land to produce products, and periodic mentoring to foster and assist partners until they succeed in cultivating healthy vegetables by utilizing vacant land to achieve optimal results. Healthy vegetable cultivation application of healthy vegetable cultivation technology with land utilization and healthy vegetable cultivation skills there is an increase in understanding, this is known from the results of the questionnaire distributed, the advantage of utilizing narrow yard land Innovation Technology can maintain family food health and increase family economy as evidenced by the results of joint harvests carried out together and periodically.